2010
DOI: 10.1021/jo100570x
|View full text |Cite
|
Sign up to set email alerts
|

Basicity of Pyridine and Some Substituted Pyridines in Ionic Liquids

Abstract: The equilibrium constants for ion pair formation of some pyridines have been evaluated by spectrophotometric titration with trifluoroacetic acid in different ionic liquids. The basicity order is the same in ionic liquids and in water. The substituent effect on the equilibrium constant has been discussed in terms of the Hammett equation. Pyridine basicity appears to be less sensitive to the substituent effect in ionic liquids than in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Cheng et al. have measured the p K a values of a series of carbon acids, benzoic acids and sulfonamides in three bis(trifluoromethylsulfonyl)imide (triflimide, Tf 2 N)‐based ILs and in 1‐butyl‐3‐methylimidazolium trifluoromethanesulfonate ([BMIM][OTf]), by using the overlapping indicator method and avoiding the previously suggested ion‐pairing effect in ILs . Indeed the carbanions of the C−H acids used as substrate or indicators are sterically hindered and largely charge‐delocalised, properties that reduce the occurrence of ion‐pair formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng et al. have measured the p K a values of a series of carbon acids, benzoic acids and sulfonamides in three bis(trifluoromethylsulfonyl)imide (triflimide, Tf 2 N)‐based ILs and in 1‐butyl‐3‐methylimidazolium trifluoromethanesulfonate ([BMIM][OTf]), by using the overlapping indicator method and avoiding the previously suggested ion‐pairing effect in ILs . Indeed the carbanions of the C−H acids used as substrate or indicators are sterically hindered and largely charge‐delocalised, properties that reduce the occurrence of ion‐pair formation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reaction is faster in ILs than in conventional organic solvents, with rate constants higher than those expected on the basis of the p K a values . This result could suggest a higher basicity of the catalyst in ILs than in conventional organic solvents but we were aware that the p K a values collected in aqueous solution do not adequately describe the acid–base strength of species in ILs, due to the peculiar IL–solute interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Chiappe and collaborates have used a Brønsted‐type correlation to understand the mechanism of the base‐catalyzed enolization reaction of 2‐nitrocyclohexanone using substituted pyridines in several ILs. They found that the β values (β > 0.9) for this reaction agree with a mechanism via solvent‐stabilized enolate‐like transition state when ILs are the reaction media .…”
Section: Introductionmentioning
confidence: 99%
“…In nucleophilic substitutions reactions, the Brønsted equation (log k vs. p K a of amine) and particularly the charge developed on the nucleophilic atom from reactants to the transition state (the slope of the Brønsted‐type plot, β) has been a very good tool to determine reaction mechanisms in water and in organic solvents . There is a great deal of information in the literature about β values for these reactions in conventional solvents; nevertheless, the information is scarce for the same reactions in ILs .…”
Section: Introductionmentioning
confidence: 99%